A Validated RP HPLC-PAD Method for the Determination of Hederacoside C in Ivy-Thyme Cough Syrup - Ayman Khdair; Mohammad K. Mohammad; Khaled Tawaha; Eman Al-Hamarsheh; Hatim S. AlKhatib; Bashar Al-khalidi; Yasser Bustanji; Samer Najjar; Mohammad Hudaib (International Journal of Analytical Chemistry)
A simple reversed phase high-performance liquid chromatographic (RP-HPLC) method coupled with a photodiode array detector (PAD) has been developed and validated for the analysis of hederacoside C, the marker of ivy plant, in Ivy-Thyme cough syrup. Separation of hederacoside C was achieved using a Phenomenex-Gemini C18 column isothermally at 40∘C. A mobile phase system constituted of solvent A (water: acetonitrile: orthophosphoric acid (85%), 860 : 140 : 2 v/v) and solvent B (acetonitrile: orthophosphoric acid (85%), 998 : 2 v/v) was used, at gradient conditions, at a flow rate of 1.5 mL/min. Analysis was performed using UV-detection (205 nm). The method was linear over the range (0.03–0.15) mg/mL of hederacoside C (𝑟=0.9992). Repeatability and intermediate precision were acceptable (RSD <2%). Limits of detection (LOD) and quantitation (LOQ) were 0.011 and 0.032 mg/mL, respectively. Percentage recovery was found to lie between 99.69% and 100.90% (RSD <2%). The method was also proved to be specific (peak-purity coeﬃcient=0.996).